Validating the Theory of Planned Behavior in Sustainability and Analyzing Gender and Regional Disparities - Mutreja, Kushagra; Gupta, Keshab; Mukherjee, Ishaan; Mehrotra, Keshav (European Journal of Sustainable Development, 2025)
This study investigates the applicability of the Theory of Planned Behavior (TPB) in analyzing sustainable behavior and examines gender-based disparities and regional disparities in sustainability practices. Using survey data from six Indian states, the paper validates TPB's effectiveness in predicting sustainable behavior by analyzing attitudes, perceived behavioral control, subjective norms, and behavioral intentions. Additionally, the paper explores gender differences by quantifying responses to key sustainability-related decisions, revealing that males are more inclined toward financial sustainability investments, while females demonstrate stronger engagement in household-level sustainable practices. Furthermore, the regional analysis highlights that respondents from Odisha and Bihar exhibit greater adherence to sustainable practices, likely due to cultural upbringing and early childhood teachings. By combining statistical validation of TPB with numerical scoring for gender and regional disparities, this study provides actionable insights for policymakers and sustainability advocates. Keywords: Theory of planned behavior (TPB), Sustainable practices, Regional-disparity, Gender-Disparity